STUDYING THE NEEDS OF FAMILIES RAISING CHILDREN WITH CEREBRAL PALSY: Received: 29th July 2025, Revised: 4th August 2025, 2nd December 2025, Accepted: 8th December 2025, Date of Publication: 24th December 2025 - Munavvar Askarova (LIFE: International Journal of Health and Life-Sciences, 2025)
Raising a child with cerebral palsy (CP) is a complex task that requires significant physical, emotional, and financial resources. This article examines the basic needs of families raising children with cerebral palsy, including medical, psychological, social, and financial support. An initial study of the key problems faced by such families has been conducted and recommendations for their solution have been proposed.